Effect of sowing rate and date on establishment and growth of Trichloris crinita, a native American pasture grass from arid environments, in the Arid Chaco of Argentina = Efecto de la densidad y fecha de siembra en el establecimiento y crecimiento de Trichloris crinita, una gramínea forrajera nativa de ambientes áridos de las Américas, en el Chaco Árido de Argentina - Dominguez, Deolindo Luis Esteban; Namur, Pedro Ramón; Cavagnaro, Pablo (International Center for Tropical Agriculture (CIAT), 2024)
In arid regions, revegetation with locally adapted native species can improve forage production and help ameliorate soil degradation. We investigated the effects of 3 sowing dates and 3 sowing rates of Trichloris crinita cv. Chamical-INTA, a perennial forage grass native to arid and semi-arid regions, on pasture establishment parameters in the Argentinian Arid Chaco phytogeographical region. Sowing date significantly influenced plant density and soil coverage at the end of the growing season, with the latest sowing date increasing mean plant density and soil coverage by 42‒66% and 16‒38%, respectively, relative to the 1st and 2nd dates. Conversely, the later sowing dates (2nd and 3rd dates) exhibited significantly lower mean values for all plant growth-related traits, i.e. tillers per plant, plant height and percentage of flowering plants. Sowing rate had a strong effect on plant density at the end of the growing season but not on plant growth parameters. Under the conditions of this study, using intermediate sowing densities (7.5 kg seed/ha) and sowing early in the season, when temperatures were still mild, delivered the best results in terms of pasture density and establishment efficacy. Early sowing resulted in a greater percentage of flowering plants and seed set prior to the first winter frosts, which should ensure ongoing establishment of plants in the next wet season. Longer-term studies to examine the survival of plants and possible increase in plant density over time are necessary to determine if this procedure has sustainable benefits for pastures in the area.